THE APPLICATION OF COOPERATIVE LEARNING MODEL THINK TALK WRITE (TTW) TYPE ON ECOSYSTEMS TO INCREASE LEARNING RESULT OF JUNIOR HIGH SCHOOL STUDENTS - Lilik Mawartiningsih; Uswatun Sholikah (EDUSAINS, 2018)
PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA  SEKOLAH MENENGAH PERTAMA (SMP) AbstractThis study aims to improve biology learning outcomes to be better, both individual values and classical values. the researcher uses the TTW (think talk write) model, which is in this learning. Students are asked to make notes from the reading result individually (think). Students then interact and collaborate with friends to discuss the discussed tasks previously shared Teacher (talk). Furthermore, the students write the result of the discussion (write). The research method used is Classroom Action Research Method (PTK), This class is carried out in 2 cycles. The subjects of the study were the students of class VII A Junior High School Nurul Anwar Pakel Village, Montong District, Tuban Regency in the academic year 2016/2017, which numbered 28 students. The instrument used in this study is the test of learning and observation. Learning result test is used to measure student's success, observation is used through observation format to measure teacher and student performance in learning. The results showed an increase in value between before the study, cycle I and cycle II. Previously, before the research the average value of students is only 62.90, then the value of the cycle I score in the average student obtained 75,18 with 72% complete learning. The second cycle average value increased to 81,10 with 87.50% complete learning. Thus it can be concluded that student learning outcomes both individually and classically can be improved through the TTW learning model, it is suggested that biology learning with this approach can be used as an alternative method of teacher in delivering the subject matter especially on biology.AbstrakPenelitian ini bertujuan untuk meningkatkan hasil pembelajaran biologi menjadi lebih baik, baik nilai individu maupun nilai klasik. Peneliti menggunakan model TTW (Think Talk Write), yang dalam pembelajaran ini. Siswa diminta membuat catatan dari hasil bacaan satu per satu (berpikir). Siswa kemudian berinteraksi dan berkolaborasi dengan teman-teman untuk mendiskusikan tugas-tugas yang dibahas yang sebelumnya dibagikan Guru (bicara). Selanjutnya, siswa menulis hasil diskusi (menulis). Metode yang digunakan Penelitian Tindakan Kelas (PTK), dalam 2 siklus. Subyek penelitian siswa kelas VII A SMP Negeri Nurul Anwar Pakel Desa, Kecamatan Montong, Kabupaten Tuban pada tahun akademik 2016/2017, yang berjumlah 28 siswa. Instrumen yang digunakan adalah tes pembelajaran dan observasi. Tes hasil belajar digunakan untuk mengukur keberhasilan siswa, observasi digunakan melalui format observasi untuk mengukur kinerja guru dan siswa dalam pembelajaran. Hasilnya menunjukkan peningkatan nilai antara sebelum penelitian, siklus I dan siklus II. Sebelum penelitian nilai rata-rata siswa hanya 62,90, maka nilai siklus I skor pada rata-rata siswa 75,18 dengan tuntas belajar tuntas 72%. Nilai rata-rata siklus kedua meningkat menjadi 81,10 dengan 87,50% menyelesaikan pembelajaran. Dapat disimpulkan bahwa hasil belajar siswa baik secara individu maupun klasik dapat ditingkatkan melalui model pembelajaran TTW, disarankan agar pembelajaran biologi dengan pendekatan ini dapat digunakan sebagai metode alternatif guru dalam menyampaikan materi pelajaran terutama pada biologi.